The 4‐cysteine zinc‐finger motif of the RNA polymerase regulator DksA serves as a thiol switch for sensing oxidative and nitrosative stress. Issue 4 (7th January 2014) - Henard, Calvin A.; Tapscott, Timothy; Crawford, Matthew A.; Husain, Maroof; Doulias, Paschalis‐Thomas; Porwollik, Steffen; Liu, Lin; McClelland, Michael; Ischiropoulos, Harry; Vázquez‐Torres, Andrés
Summary We show that thiols in the 4‐cysteine zinc‐finger motif of DksA, an RNA polymerase accessory protein known to regulate the stringent response, sense oxidative and nitrosative stress. Hydrogen peroxide‐ or nitric oxide (NO)‐mediated modifications of thiols in the DksA 4‐cysteine zinc‐finger motif release the metal cofactor and drive reversible changes in the α‐helicity of the protein. Wild‐type and relAspoT mutant Salmonella, but not isogenic dksA‐deficient bacteria, experience the downregulation of r‐protein and amino acid transport expression after NO treatment, suggesting that DksA can regulate gene expression in response to NO congeners independently of the ppGpp alarmone. Oxidative stress enhances the DksA‐dependent repression of rpsM, while preventing the activation of livJ and hisG gene transcription that is supported by reduced, zinc‐bound DksA. The inhibitory effects of oxidized DksA on transcription are reversible with dithiothreitol. Our investigations indicate that sensing of reactive species by DksA redox active thiols fine‐tunes the expression of translational machinery and amino acid assimilation and biosynthesis in accord with the metabolic stress imposed by oxidative and nitrosative stress. Given the conservation of Cys114, and neighbouring hydrophobic and charged amino acids in DksA orthologues, phylogenetically diverse microorganisms may use the DksA thiol switch to regulate transcriptional responses to oxidative and nitrosative stress.